2020
DOI: 10.1111/ppa.13310
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of 43‐year old samples of Plantago lanceolata show that Plantain virus X is synonymous with Actinidia virus X and is widely distributed

Abstract: Plantain virus X was first recognized by the ICTV as a species in the genus Potexvirus in 1982. However, because no sequence was available for plantain virus X (PlVX), abolishing the species was proposed to the Flexiviridae working group of the ICTV in 2015. This initiated efforts to sequence the original isolates from Plantago lanceolata samples. Here we report the full‐genome sequencing of two original isolates of PlVX, which demonstrate that the virus is synonymous to Actinidia virus X, a species previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Many of these pathogens have been included in plant health regulations around the globe, and some are even recognized as species. However, with the increased use of non-targeted sequence-based detection, combined with the limited resources available for time consuming and costly biological characterization work there are examples of 'rediscovery' , such as the case of plantain virus X and Actinidia virus X, two synonymous viruses discovered at opposite sides of the globe, over 30 years apart, and in unrelated hosts (Hammond et al 2020), a case study pulling together two recognized species discovered 30+ years apart (pre and post sequencing eras) where the conclusions being drawn on the risk of the latter were incorrect due to lack of knowledge on the first non-sequenced report. Historic isolate collections can be an invaluable resource.…”
Section: Issues For Diagnosticsmentioning
confidence: 99%
“…Many of these pathogens have been included in plant health regulations around the globe, and some are even recognized as species. However, with the increased use of non-targeted sequence-based detection, combined with the limited resources available for time consuming and costly biological characterization work there are examples of 'rediscovery' , such as the case of plantain virus X and Actinidia virus X, two synonymous viruses discovered at opposite sides of the globe, over 30 years apart, and in unrelated hosts (Hammond et al 2020), a case study pulling together two recognized species discovered 30+ years apart (pre and post sequencing eras) where the conclusions being drawn on the risk of the latter were incorrect due to lack of knowledge on the first non-sequenced report. Historic isolate collections can be an invaluable resource.…”
Section: Issues For Diagnosticsmentioning
confidence: 99%
“…PSbMV was only found in three symptomatic samples and PNYDV was not found in this initial work. Sequencing of historic isolates can also give greater understanding of the plant health impact of more recent virus discoveries [58]. The finding of TuYV and SbDV in a historical isolate shows that these viruses have been present in the UK for at least a decade.…”
Section: Discussionmentioning
confidence: 99%
“…Later, when other potyvirus sequences were compared with it, a 79% nt identity was found between ArVY and an arracacha mottle virus isolate from Brazil in 2013 (Orílio et al, 2009(Orílio et al, , 2013, revealing the Brazilian virus to be ArVY (Adams et al, 2018b). Another example of (a) was revealed recently when 43-year-old samples of Plantago lanceolata infected with the plantain virus X (PlVX; genus Potexvirus) were sequenced (Hammond et al, 2020). This resulted in the finding that PlVX and Actinidia virus X (AVX; genus Potexvirus) sequences belonged to the same virus.…”
Section: Viruses Incorrectly Renamedmentioning
confidence: 97%
“…Subsequently, AVX was detected in Ribes nigrum plants with symptoms (James & Phelan, 2016); previously, AVX had not been reported in Europe, and so the virus was considered a possible quarantine risk to the EU. Whilst investigating PlVX in the UK, samples from the original study were located in an historical virus isolate collection; virus from these samples was sequenced and it was demonstrated that PlVX and AVX were synonymous, with subsequent research showing the virus to be widespread in the environment in northern Europe (Hammond et al, 2020). This example suggests a further, as yet underexploited, application of historical isolate sequencing is its use in establishing the baseline presence of a virus in a given geographic area.…”
Section: Supp Orting Pl Ant He Alth Reg Ul Ati On S and Ris K A Ss mentioning
confidence: 99%